Skilled Migration Policy and the Labour Market Performance of Immigrants - Massimiliano Tani (Institute of Labor Economics (IZA), 2017)
This paper studies whether migration policy, besides managing a country's population size, is a suitable tool to influence immigrants' labour market outcomes. To do so, it uses a migration policy change that occurred in Australia in the late 1990s and data collected by the Longitudinal Survey of Migrants to Australia. The statistical techniques employed in the empirical analysis consistently reveal that the policy change has no detectable impact on the employment rate, wages, over-education, occupational downgrading, and (self-reported) use of skills for male immigrants, who account for about 75% of the sample, while they have a modest short-term positive impact on female immigrants. These results support the view that migration policy is an ineffective policy tool to influence migrants' labour market outcomes. However, the economic relevance of making an effective use of migrants' skills provides scope for close coordination between immigration and employment policy to ensure that efforts in attracting foreign talent are not dissipated by labour market frictions and other inefficiencies.
Keywords: J15; J24; 330; skilled immigration; labour market; over-education; immigration policy